Des négociations internationales aux stratégies locales - Edith Kauffer (Territoire en Mouvement, 2012)
This paper tries to analyze equity in Mexican climate policy from international dimension to local strategies, including recent federal policy. It distinguishes substantive and procedural equity and contrasts international, national and social equity depending on the area.In spite of the centrality of equity in international documents, climate policy focuses more on mitigation than adaptation, which evidences difficulties to concretize procedural international equity. At national scale and contrary to Mexican international position, it scarcely follows substantive and procedural equity insofar that climate policy agenda is defined by federal government to down to states. Eventually, social equity that integrates all stakeholders’ participation is revised for Chiapas and Tabasco. The analysis evidences difficulties for states to conceive social heterogeneity and allows social participation in climate policy. In front of the lack of social equity, stakeholders’ mobilization expresses no traditional ideas and interests about climate policy.